FAIR TRIAL FOR PERSONS WITH DISABILITIES: IDEALITY VS REALITY - Amalia Nugraheni, Novie; Kristanto, Andri (Journal Philosophy of Law, 2024)
The purpose of this research is to analyze the barriers in fulfilling the rights of persons with disabilities in the fair trial process to provide legal protection to persons with disabilities. The type of research used in this study is juridical normative research using secondary data obtained from previous research. The data analysis method used is qualitative by collecting data in the form of applicable laws, books, journals related to persons with disabilities and law enforcement, and interviews with stakeholders involved. The research results show that fair trials for persons with disabilities are still an ideal that has not been fully achieved. Real commitment and action from the government, law enforcement, and society are needed to ensure the protection of the rights of persons with disabilities in the justice system. There is still a lack of understanding and awareness of their needs, but increased awareness and training can help address this issue. Fair trials must consider limited physical accessibility and alternative communication facilities, and ensure adequate training for court staff. Concrete actions are needed to improve awareness, training, and accessibility in the justice system.